Preface: 3rd International Conference on Culture, Education, Psychology and Communications (CEPC 2024) - Jeremy, Jacqueline; Qiu, Tao (Transactions on Social Science, Education and Humanities Research, 2024)
Thanks for your participations in 2024 3rd International Conference on Culture, Education, Psychology and Communications (CEPC 2024), which was held during July 20-21, 2024, in Nagoya, Japan. This conference brought together innovative academics and experts in the fields of cultural heritage, cultural communications, linguistics, humanities, history, education science, psychology, new media, and social sciences to a common forum. The primary goal of the conference is to promote research and developmental activities and another goal is to promote scientific information interchange between researchers, developers, engineers, students, and practitioners working all around the world. We are confident that the participants benefited from the theoretical insights, practical knowledge and personal contacts that will help them to build a long-term and sustainable communication among researchers and practitioners in the related scientific areas. It is one of the leading international conferences for presenting novel and fundamental advances. CEPC 2024 offered a chance for scientists and educators working in different areas and help them advance their own research and forge new professional relationships and collaborations. This conference including keynote speech, oral presentations, poster presentations and Q & A section. With warmest regards, CEPC Organizing Committees Nagoya, Japan